An Overview of Oil Production Stages: Enhanced Oil Recovery Techniques and Nitrogen Injection - Alagorni, Abubaker Hamza; Zulkefli, Yaacob; Nour, A. H. (IACSIT Press, 2015)
During the life oil wells, production process usually passes three stages. Primary recovery uses the natural source of energy. Pumps and gas lifting are involved in the primary recovery. The main purpose of secondary recovery process is to maintain the reservoir pressure by either a natural gas flooding or water flooding. The rise in world oil prices has encouraged the producers to use the new technical developments. Enhanced oil recovery (EOR) is a collection of sophisticated methods, to extract the most oil from a reservoir. EOR can be divided into two major types of techniques: thermal and non-thermal recovery. Each technique has a specific use in a certain type of reservoirs. Among non-thermal techniques is the gas flooding, where gas is generally injected single or intermittently with water. Flue gas and nitrogen have only limited application as agents of a miscible displacement in deep and high pressure reservoirs. Although new development processes such as water alternating gas (WAG) or Simultaneous water alternating gas (SWAG), are implemented, there are still some problems encountered by EOR engineers. This paper is discussing the last updating in this field.